Using phonetic knowledge in tools and resources for Natural Language Processing and Pronunciation Evaluation - Almeida, Gustavo Augusto de Mendonça (2016)
This thesis presents tools and resources for the development of applications in Natural Language Processing and Pronunciation Training. There are four main contributions. First, a hybrid grapheme-to-phoneme converter for Brazilian Portuguese, named Aeiouadô, which makes use of both manual transcription rules and Classification and Regression Trees (CART) to infer the phone transcription. Second, a spelling correction system based on machine learning, which uses the trascriptions produced by Aeiouadô and is capable of handling phonologically-motivated errors, as well as contextual errors. Third, a method for the extraction of phonetically-rich sentences, which is based on greedy algorithms. Fourth, a prototype system for automatic pronunciation assessment, especially designed for Brazilian-accented English.